ChatGPT application in explaining the English articles to Ukrainian students - Alexandrivna, Koval Natalia; Lilita, Kokkina; Borysivna, Grodska Elina; Yuhimivna, Tsapenko Ludmila; Victorivna, Lebedieva Olena; Victorivna, Gvozd Olga (Edelweiss Applied Science and Technology, 2025)
The article deals with the description of an experiment, a kind of empirical study, which was carried out in one of the Polytechnic Universities of Ukraine. It (the experiment) involved ChatGPT’s participation in the process along with the teachers and students. The group included both humanitarian and engineering students. The goal of the article was as follows: to identify whether the ChatGPT system alone, without a teacher’s participation, is capable of freely communicating with students, answering their possible questions, and satisfactorily explaining any grammatical material. The results demonstrated that in spite of some shortcomings that were evident in presenting outdated data and a lack of necessary details, ChatGPT’s importance as an unlimited informational resource can hardly be overestimated. However, the experiment has proven another fact as well – it is the teacher who was a real promoter of the explanation strategy in the educational process, which manifested in close communication both with the students and ChatGPT, making him a real intermediate link between them.